Pertanggungjawaban Pidana Pelaku Cyberbullying Menggunakan Fake Account - barid zein, izzata; Laily Mufid, Firda; Winiari Wahyuningtyas, Yuli; Manab, Abd (Prodi Ilmu Hukum Fakultas Hukum Universitas Islam Jember, 2024)
Formulation of the problem of law enforcement againstcyberbullying perpetrators and criminal liability for cyberbullyingperpetrators who use fake accounts with the aim of finding out lawenforcement against cyberbullying perpetrators. and to find outcriminal liability for perpetrators of cyberbullying. using a FakeAccount. The method in this research uses a normative juridicalresearch type. Conclusions from this research. Law enforcementagainst cyberbullying crimes is contained in the Criminal Code andLaw Number 11 of 2008 concerning Information and ElectronicTransactions, there are several articles related to forms ofcyberbullying relating to prevention, prosecution and prosecutionof perpetrators and victims. The issuance of the SKB on the ITELaw serves as a guide for law enforcement. The articles contained inthe SKB can be studied objectively by law enforcers and resolvecases without having to be submitted to court and strengthen theposition of criminal justice as the ultimum remidium, namely thatcriminal punishment or sanctions are an alternative or last resortin law enforcement. . The purpose of forming this SKB is tomaintain a clean, healthy, productive and fair Indonesian digitalspace. The burden of responsibility is imposed on the perpetrator ofa criminal act in connection with the basis for imposing criminalsanctions. The nature of responsibility for his actions is against thelaw and there is no excuse. This issue of responsibility is stated inArticle 44 of the Criminal Code.